Penanggulangan Bencana sebagai Soft Power dalam Diplomasi Indonesia - Ratih Herningtyas (Universitas Muhammadiyah Yogyakarta, 2014)
This paper aims to describe how the issue of disasters in Indonesia can be modified into a positive social capital to solve social, economic, political and social culture’s problems in disaster prone areas. This paper found that Indonesia’s disaster managements get worldwide recognition and increases Indonesia’s competitiveness toward other countries. These recognitions become the sources of Indonesia’s soft power, and can be used as a strategic instrument to build regional cooperation and international collaboration to improve infrastructure that can reduce the degree of disasters’ material and immaterial losses.